PERAN PERBANKAN TERHADAP PETANI KELAPA SAWIT DI KECAMATAN SOSA KABUPATEN PADANG LAWAS SUMATERA UTARA - Rischa Efidayanthi (Departemen Ekonomi Pembangunan USU, 2013)
Districts Sosa is an area that is in the province of North Sumatra which has potential in agriculture. Therefore, agricultural development is absolutely necessary given the agricultural sector is the motor of value -added and diversified production in other sectors of the economy. Role of banks to oil palm growers have an impact on farmers' incomes in the oil palm sub-district Sosa. The purpose of this study was to determine the effect of initial capital, capital of the bank and how much land to oil palm farmers in the sub-district Sosa old fields, using the descriptive method, deductive and primary data. The data collected through interviews and questionnaires. The Method in analyzing the role of banking to oil palmfarmers in sub-district Sosa is a method of Ordinary Least Square (OLS) with the analytical tools to process data by using SPSS 16.00 for windows. The results showed that the role of banks to oil palm growers positive effect on the income of oil palm growers in the sub-district Sosa, it can be seen from the R-square is 0.657 ( 65.7 % ).Keywords: Role of Banking, Oil Palm, Revenue.